2015
DOI: 10.1186/s12876-015-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of serum des-gamma-carboxyprothrombin in the diagnosis of hepatocellular carcinoma among Nigerians, a case–control study

Abstract: BackgroundHepatocellular Carcinoma (HCC) is a common malignancy occurring globally but with a dismal prognosis. Des-gamma-carboxyprothrombin (DCP) has been reported to be more sensitive and specific than Alpha-fetoprotein (AFP) in the diagnosis of HCC among the White population. Its efficacy among the Black population is yet to be established. The aim of this study therefore, was to determine the relative sensitivity and specificity of des-gamma-carboxyprothrombin and alpha-fetoprotein in the diagnosis of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A summary of notable findings is as follows. First, both PIVKA-II and AFP levels are significantly elevated in unresectable HCC, with clear distinctive levels from healthy controls, similarly reported elsewhere ( Ette et al, 2015 ). A previous study has also reported an assessment of biomarkers between patient and control to avoid misleading interpretation ( Rutjes et al, 2005 ; Husnain et al, 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…A summary of notable findings is as follows. First, both PIVKA-II and AFP levels are significantly elevated in unresectable HCC, with clear distinctive levels from healthy controls, similarly reported elsewhere ( Ette et al, 2015 ). A previous study has also reported an assessment of biomarkers between patient and control to avoid misleading interpretation ( Rutjes et al, 2005 ; Husnain et al, 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…DCP has been reported to be more sensitive and specific than AFP for the diagnosis of HCC with a cutoff of > 40 mAU/mL[92]. However, its role in the detection of small tumors and early HCC is unclear as various studies have utilized different cutoff values for DCP and AFP[92-94]. Moreover, it has never been studied in non-cirrhotic patients.…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, Ette et al 40 noted the high sensitivity of des-gamma-carboxyprothrombin (DCP) in African patients relative to AFP in detecting HCC (especially tumours greater than 3cm) without combining both tumour markers.…”
Section: Discussionmentioning
confidence: 99%